The ethics of corporate hypocrisy: An experimental approach - Johanna Jauernig; Matthias Uhl; Vladislav Valentinov (Futures, 2021)
In the current landscape of management and business ethics scholarship, a prominent type of dissimulation is exemplified by corporate hypocrisy. The concept of corporate hypocrisy brings traditional morality to bear on the institutions of the modern society and thereby emphasizes the contested relationship between the research programs of individual and institutional ethics. Assuming that morality in the modern society resides in institutions rather than individuals, institutional ethics emphasizes limits to the ability of traditional morality to come to terms with the moral complexity of the market economy. The case of corporate hypocrisy shows however that traditional morality nurtures individual sensitivity to immoral behaviors which may undermine the modern institutional fabric theorized by institutional ethics. This argument is supported by our central experimental finding that the moral evaluation of individual and corporate hypocrisy is driven by essentially the same psychological mechanisms. Moreover, the experiment showed that both corporate and individual hypocrisy are condemned stronger than frankly wrong behavior even if their consequences are identical.
Keywords: 330; moral evaluation; institutional ethics; behavioral ethics; Greenwashing; (self-) deception